Physical activity and mortality in patients with colorectal cancer: a meta-analysis of prospective cohort studies. Issue 1 (January 2020) - Qiu, Shumin; Jiang, Chongmin; Zhou, Lin
Abstract : The association between physical activity (PA) and colorectal cancer (CRC) patients' survival is inconsistent. We conducted a systematic review and meta-analysis to summarize published articles on this issue. We performed a comprehensive search of the PubMed, Embase, and Web of Science databases for relevant articles through 28 February 2018. The summary hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated using a random-effects model. Eighteen prospective cohort studies were included in the meta-analysis, with a total of 9257 cases of total mortality (TM) and 4015 cases of colorectal cancer-specific mortality (CRCSM) among 31 873 CRC survivors and 557 150 general populations. Among CRC survivors, the highest versus the lowest levels of prediagnosis PA showed decreased risks of TM (summary HR = 0.81, 95% CI: 0.76–0.87, I 2 = 1.8%) and CRCSM (summary HR = 0.85, 95% CI: 0.77–0.98, I 2 = 0), respectively. Significant risk reductions for TM and CRCSM were also demonstrated for postdiagnosis PA (HR = 0.63, 95% CI: 0.54–0.74; and HR = 0.64, 95% CI: 0.47–0.88, respectively). The inverse association between prediagnosis PA and cancer mortality was more pronounced for colon cancer than that for rectal cancer ( P = 0.08). The summary HRs (95% CIs) of TM were 0.89 (0.83–0.97) and 0.79 (0.69–0.90) per 10 metabolic equivalent task-h/week increase in prediagnosis and postdiagnosis PA, respectively. Our meta-analysis provides comprehensive evidence that PA performed before or after cancer diagnosis is related to reduced mortality risk among CRC survivors. Abstract : Supplemental Digital Content is available in the text.